Appropriateness and Pattern of Antibiotic Prescription in Pediatric Patients at Adigart General Hospital, Tigray, Ethiopia. (12th April 2021) - Yehualaw, Adane; Taferre, Chernet; Bantie, Abere Tilahun; Demsie, Desalegn Getnet
Abstract : Background . Inappropriate and unnecessary use of antibiotics can increase morbidity, mortality, medical expenses or patient cost, and microbial antibiotic resistance. However, in developing countries like Ethiopia, information regarding appropriateness of antibiotic prescribing pattern to guide improvement strategies is scant. Objective . The aim of this study was to assess appropriateness and pattern of antibiotic prescription in pediatric patients at pediatric ward of Adigrat General Hospital. Methods . Hospital-based retrospective cross-sectional study was conducted to assess the antibiotic prescribing pattern in pediatric inpatient and outpatient ward of Adigrat General Hospital from December 1, 2018 to April 30, 2019. Data was collected by using structured data collection checklist, and the systematic random sampling technique was employed to enroll the required sample size during the study period. Appropriateness of drug use in pediatrics was evaluated using Ethiopian Standard Treatment guideline and WHO pediatric guideline. Result . A total of 692 pediatric patients' medical charts were reviewed. The median age of patients on antibiotics was 3.26 years (IQR: 2-4). Majority (49.13%) of the patients were hospitalized for 5-9 days. SCAP (195), tonsillitis (114), and cellulitis (99) were most frequently encountered pediatric diseases. Penicillins (37.86%) followed by cephalosporins (31.79%) antibiotics were the most prescribed antibiotics in pediatric wards. This study also showed that ceftriaxone and ceftriaxone+amoxicillin were the most frequently used single and combination antibiotics, respectively. The prescribing practices were not stick to WHO core indicators and standards. Inappropriate prescription of antibiotics was observed in 28.3% of patients. Advanced age of children, children aged between 6 to 10 years (AOR = 3.225 ; CI = 1.080 − 9.630 ; P = .036 ) and 11-18 years (AOR = 18.691 ; CI = 5.156 − 67.756 ; P = .000 ), was the independent determinant of inappropriate drug use. Conclusion . Inappropriate antibiotic prescribing was encountered in 28.3% of children. The rate of generic prescription was not in line with WHO recommendation. Advanced age of children was the independent factor for inappropriate use of antibiotics.